2017
DOI: 10.1371/journal.pone.0170259
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Toxicity of Long-Course Oral Corticosteroids in Children

Abstract: BackgroundLong courses of oral corticosteroids are commonly used in children in the management of chronic conditions. Various adverse drug reactions (ADRs) are known to occur with their use. This systematic review aimed to identify the most common and serious ADRs and to determine their relative risk levels.MethodsA literature search of Embase, Medline, International Pharmaceutical Abstracts, CINAHL, Cochrane Library and PubMed was performed with no language restrictions in order to identify studies where oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 126 publications
1
107
0
2
Order By: Relevance
“…Most children will have fewer comorbidities complicating the use of immunomodulatory agents such as ciclosporin. As such, while systemic CS should be used rarely for severe AD in general, their use should be even more limited in children, particularly given concerns regarding infection, growth delay and increased rates of obesity …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most children will have fewer comorbidities complicating the use of immunomodulatory agents such as ciclosporin. As such, while systemic CS should be used rarely for severe AD in general, their use should be even more limited in children, particularly given concerns regarding infection, growth delay and increased rates of obesity …”
Section: Discussionmentioning
confidence: 99%
“…Based on their use in other conditions, the long‐term intermittent use of systemic CS is well known to cause a multitude of side‐effects, and even use for 30 days or less has been associated with increased rates of sepsis, venous thromboembolism and fracture . A recent systematic review of studies in children taking systemic CS for > 2 weeks found significant increases in infections, growth delay and obesity …”
Section: Approach To Systemic Corticosteroid (Cs) Use In Atopic Dermamentioning
confidence: 99%
“…18 Evidences of HPA dysfunction due to ICS have been reported in the literature in up to 40% 10,19-23 of cases and due to OCS in up to 80%. 24 Symptomatic AS can be seen in children treated with inhaled beclomethasone even at initial doses as low as 200 mcg/day, depending on individual sensitivity and genetic predisposition. 23 The Canadian Society of Allergy and Clinical Immunology recommends screening for AS in children receiving high-dose ICS based on morning serum cortisol level.…”
Section: Discussionmentioning
confidence: 99%
“…In children, weight gain, growth retardation, and Cushingoid features are the most frequent adverse reaction to chronic oral glucocorticoid use, but a recent meta-analysis that included a total of 6817 children noted a 21% incidence of decreased bone mineral density [40]. Growth retardation, whether directly or through suppression of the hypothalamic-pituitary axis or of sex steroid hormone production, puts children at considerable risk of osteoporosis in adulthood, as peak bone mass is achieved in late adolescence and early adulthood.…”
Section: Special Consideration: Children On Steroidsmentioning
confidence: 99%